Cloud-based sustainable management of electrical and electronic equipment from production to end-of-life. Issue 1 (7th January 2019) - Conti, Massimo; Orcioni, Simone
Abstract : Purpose: The purpose of this paper is to describe a system and a database structure for the tracing of the waste of electric and electronic equipment (WEEE) using radio-frequency identification tags. Design/methodology/approach: The problems related to the management of WEEE and the international directives have been presented and analyzed. The authors propose a traceability system to extend the tracing in the reverse logistics. Findings: The proposed systems allow a more efficient management of the reuse, repair and recycle phase of the products and components, thus reducing the disposal of the electric and electronic equipment. There are many possible positive impacts of the system. The authors investigate, in particular, the impact of the single component tracing on the disposal cost reduction and on the reliability improvement using reused components. Research limitations/implications: The system has been tested in the production chain of a company that produces electronic equipment for elevators. Up to now, the results and impact are limited to the company. Practical implications: The system has been applied in the management of reused components of a specific company. The immediate result was that the system allowed the redesign of the electronic product with a cost reduction and reliability improvement. Social implications: The authors think that the proposed solution allows a step forward in the reduction of WEEE. Originality/value: The database structure and the web application, used to track the entire working life of an electronic appliance, are original. Original is also the idea of tracing all the single components of the electronic products.